Pengembangan Media Pembelajaran E-Komik Berbasis Problem Based Learning (PBL) Terhadap Kemampuan Pemecahan Masalah - Irianti Yolan; Rahman Haryadi; Wandra Irvandi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The purpose of this study was to develop Problem Based Learning (PBL) based E-Comic learning media on Problem Solving Ability that is valid, practical, and effective on student learning outcomes in statistics material in class XII at SMA Negeri 1 Sungai Laur. The method used is the ADDIE method. The subjects of this study were 29 class XII students of SMA Negeri 1 Sungai Laur, 3 material and media experts. The instruments used in this study were in the form of material expert validation sheets and media expert validation sheets, teacher response questionnaires, student response questionnaires and post-test questions based on the results of the research that had been carried out obtained the results of validation of E-Comic learning media based on Problem Based Learning (PBL). ) Regarding Problem Solving Ability has a validity level of 91.22% with very valid criteria, the practicality level of learning media is 89.60% with very practical criteria and the level of effectiveness of learning media is 93.10% with very effective criteria.